Biochemical Characterization of Collagen Extracted from the Swim Bladder of Catfish (Bagre panamensis) - Lopez S.; Salguero A.; Vargas A.; Zavala A. (European Scientific Journal, ESJ, 2018)
In the present investigation, the extraction and subsequent characterization of the collagen in the swim bladder of catfish was developed, for which a total of twelve experimental units were analyzed, distributed in three samples with four repetitions per analysis distributed under a completely randomized design with a 0,05% of significance, the size of the experimental unit 200g of lyophilized collagen. Protein, minerals, water, pH, hydroxyproline were then quantified in addition to the microbiological assays. The results obtained correspond to 76.86% of protein, 9.02% of humidity, 14.12% of ash, while for pH 4.55, hydroxyproline 44,08% and ausence of UFC/g were reported. It is determined that it can be used in food formulations to improve the texture due to its hydroxyproline content.